Opioid use after ankle fracture surgery: current trends in the United States. Issue 4 (July 2019) - Chen, Michael J.; Zhang, Steven; DeBaun, Malcolm; Fogel, Nathaniel; Bishop, Julius A.; Gardner, Michael J.
Abstract : Background: The United States opioid epidemic has been declared a national public health emergency. While opioids are frequently prescribed after ankle fracture surgery, the percentage of patients actually requiring them is unknown. Here we compare the annual percentage of patients using an opioid prescription after ankle fracture surgery over the last decade. Methods: We retrospectively queried a large private-payer database from 2007-2015 and identified 20, 992 opioid-naive patients undergoing ankle fracture surgery. We then measured the annual prevalence of opioid prescriptions over time separated into the immediate postoperative period (between 0 and 6 mo from surgery) and the prolonged period (between 6 and 12 mo from surgery). Linear regression with beta coefficients was calculated. Results: The prevalence of patients filling opioid prescriptions between 0 and 6 mo after surgery declined from 28.5% to 21.2% during the study period. The prevalence of patients filling opioid prescriptions between 6 and 12 mo after surgery declined from 2.9% to 2.3% during the study period. Conclusions: The percentage of patients utilizing opioid prescriptions after ankle fracture surgery is much lower than expected, suggesting that routine prescriptions given after ankle fracture surgery and other smaller orthopaedic procedures are not likely to be contributing to the epidemic.